220k views
5 votes
Solve the equation.
5x + 12 = -13

2 Answers

7 votes

Answer: -5

Explanation:

5x = -13 - 12

5x = -25

x = -25/5

x = -5

User Sabari
by
5.6k points
4 votes

Answer:

Simplifying

5x + 12 = -13

Reorder the terms:

12 + 5x = -13

Solving

12 + 5x = -13

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-12' to each side of the equation.

12 + -12 + 5x = -13 + -12

Combine like terms: 12 + -12 = 0

0 + 5x = -13 + -12

5x = -13 + -12

Combine like terms: -13 + -12 = -25

5x = -25

Divide each side by '5'.

x = -5

Simplifying

x = -5

Explanation:

User Debdut Goswami
by
4.6k points